(untitled) (The Review of Diabetic Studies, 2025)
Background: Continuing Professional Development (CPD) is a fundamental strategy for maintaining and enhancing nurses’ competencies, ensuring patient safety, and improving the quality of healthcare services. In Saudi Arabia, CPD has gained increased importance in response to healthcare system reforms, workforce nationalization, and mandatory professional accreditation requirements. However, evidence regarding the effectiveness of CPD programs for nurses within the Saudi context remains fragmented. Aim: This systematic review aimed to evaluate the impact of CPD programs on clinical competence, patient safety, and quality of care among nurses working in Saudi Arabia. Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. Electronic databases including PubMed/MEDLINE, CINAHL, Scopus, Web of Science, and Google Scholar were searched for studies published between 2013 and 2024. Eligible studies included quantitative, qualitative, and mixed-methods research examining CPD interventions among nurses in Saudi healthcare settings. Data extraction and quality appraisal were performed using standardized tools from the Joanna Briggs Institute. Due to heterogeneity in study designs and outcome measures, a narrative synthesis approach was applied. Results: Ten studies met the inclusion criteria. The findings indicated that CPD programs were consistently associated with improvements in nurses’ clinical competence, including enhanced knowledge, technical skills, clinical confidence, and decision-making abilities. Positive effects on patient safety were also reported, particularly in relation to adherence to safety protocols, infection control practices, medication safety, and safety culture. Improvements in quality of care—such as patient-centered care, communication, and adherence to quality standards—were observed in several studies, although these outcomes were influenced by organizational and contextual factors. Simulation-based, competency-focused, and practice-oriented CPD interventions demonstrated the most robust outcomes. Conclusion: The evidence suggests that CPD programs play a crucial role in strengthening Saudi nurses’ clinical competence and contribute positively to patient safety and quality of care. To maximize effectiveness, CPD initiatives should be contextually relevant, competency-based, and supported by organizational leadership and resources. Further longitudinal research using standardized outcome measures is recommended to assess the sustained impact of CPD on patient and organizational outcomes.